INTRODUKSI Trichoderma sp. PADA TANAMAN CABAI (Capsicum frutescens) - Irna, Ade; Hafsan, Hafsan; Alfian, Alfian (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2023)
Chili (Capsicum frutescens) is one of the most widely cultivated vegetable commodities in Indonesia. The community's need for chilies is increasing every year, but the production of chilies in Indonesia is still not sufficient for national food needs because of the high market demand. Trichoderma sp. is an antagonistic fungus that can control the growth of pathogenic fungi and increase crop production. This study aims to determine the effect of giving Trichoderma sp. as a biological agent on the growth of chili (Capsicum frutescens). This research was conducted at the South Sulawesi Horticultural Plant Seed Center. This research is a quantitative study with an experimental approach by inducing Trichoderma sp. different concentrations of 0 g, 5 gr, 10 g, and 15 g. This research uses Completely Randomized Design (CRD). The results showed that the dose of Trichoderma sp. in the treatment of 15 g/plant significantly affected the growth of chili plants. The highest concentration used as the application dose of Trichoderma sp has a positive effect on the growth of chili plants (Capsicum frutescens).